The effect of two calcium phosphate‐containing agents on the enamel resistance of permanent molars to demineralization: An experimental study - Fatemeh Molaasadolah; Zohre Sadat Hosseinipour; Fatemeh Afzali; Ardavan Parhizkar; Kiana Poorzandpoush (Wiley, 2022)
Abstract Background The main purpose of this experimental study was to determine the in vitro effects of two calcium phosphate‐containing agents (Remin Pro® and GC Tooth mousse™) on the enamel resistance of permanent molars to demineralization. Methods Fifty extracted human third molars were randomly divided into four groups; that is the control group and three case groups treated with Remin Pro®, GC Tooth mousse™, and sodium fluoride gel. The three case groups were treated with 0.25 ml of the paste associated with each experimental group for 5 min, kept in fluoride‐free artificial saliva, and incubated at 37°C for 28 days. After the treatment regimen, 10 samples of each case group were subjected to demineralization using an acetic acid‐containing solution, and remineralization using a remineralizing solution. The morphology of enamel was observed via scanning electron microscopy and their enamel calcium/phosphorus (Ca/P) ratios were measured before/after the demineralization cycle with energy‐dispersive X‐ray analysis. Data were statistically analyzed using one‐way analysis of variance and post hoc Tukey tests. Results The enamel Ca/P ratios in the case study groups were significantly higher than that of the control group before/after the demineralization regimen (p < .0001). However, the ratios were not significantly different between the case study groups after the treatment regimen and demineralization cycle (p > .05). Conclusion The outcomes of the current study indicated that all three agents seemed to increase the enamel resistance of permanent molar teeth to demineralization.